Magnetically-responsive silica–gold nanobowls for targeted delivery and SERS-based sensing. Issue 23 (26th May 2016) - Mo, Alexander H.; Landon, Preston B.; Gomez, Karla Santacruz; Kang, Heemin; Lee, Joon; Zhang, Chen; Janetanakit, Woraphong; Sant, Vrinda; Lu, Tianyu; Colburn, David A.; Akkiraju, Siddhartha; Dossou, Samuel; et al.
Abstract : A multifunctional composite magnetic nanobowl was constructed using a bottom-up approach consisting of a silica bowl and a gold exterior shell with iron oxide magnetic nanoparticles sandwiched between the silica core and gold shell. Abstract : Composite colloidal structures with multi-functional properties have wide applications in targeted delivery of therapeutics and imaging contrast molecules and high-throughput molecular bio-sensing. We have constructed a multifunctional composite magnetic nanobowl using the bottom-up approach on an asymmetric silica/polystyrene Janus template consisting of a silica shell around a partially exposed polystyrene core. The nanobowl consists of a silica bowl and a gold exterior shell with iron oxide magnetic nanoparticles sandwiched between the silica and gold shells. The nanobowls were characterized by electron microscopy, atomic force microscopy, magnetometry, vis-NIR and FTIR spectroscopy. Magnetically vectored transport of these nanobowls was ascertained by time-lapsed imaging of their flow in fluid through a porous hydrogel under a defined magnetic field. These magnetically-responsive nanobowls show distinct surface enhanced Raman spectroscopy (SERS) imaging capability. The PEGylated magnetically-responsive nanobowls show size-dependent cellular uptake in vitro .